Idade masculina: Qualidade do sêmen e fertilidade: Idade masculina X qualidade seminal - Silva, Liliane Fi. [UNESP]; Petersen, Claudia G. [UNESP]; Oliveira, Joao Batista A. [UNESP]; Mauri, Ana L.; Massaro, Fabiana C.; Cavagna, Mario; Baruffi, Ricardo L. R.; Franco Junior, Jose Gonçalves [UNESP] (My University, 2012)
The man's age seems to affect reproductive function but to a lower degree compared with the woman's age. In fact, the effect of paternal age on semen quality has been discussed, but the results are contradictory. Considering the differences in the results of studies, this review aimed to analyze the literature regarding the effect of paternal age on semen parameters (volume, concentration, motility and morphology) in sperm DnA damage in assisted reproduction results and genetic diseases.
Male age: Semen quality and fertility: Age X male semen quality
Keywords: Assisted reproduction; Male age; Seminal parameters; DNA damage; genetic disorder; infertility therapy; male fertility; paternal age; review; semen analysis; spermatozoon density; spermatozoon motility